2005
DOI: 10.1111/j.1572-0241.2005.40476.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of GERD Ultrastructural Alterations and Relief of Symptoms After Omeprazole Treatment

Abstract: Three and six months of omeprazole therapy led to a complete recovery of DIS in 92.1% and 97.4% of cases, respectively. No significant differences of DIS between NERD and EE were noted. Complete recovery of DIS was accompanied by regression of heartburn in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
157
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(169 citation statements)
references
References 21 publications
7
157
2
3
Order By: Relevance
“…When the intercellular spaces become widened, acid and pepsin refluxed from the stomach can easily penetrate the epithelial layer and stimulate noxious receptors on the afferent neurons and induce reflux symptoms [5] . An association between widened intercellular spaces and reflux symptoms has been reported [11,12] . In order to enter the mucosal intercellular spaces, acid and pepsin have to penetrate the intercellular adhesion sites of the uppermost superficial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the intercellular spaces become widened, acid and pepsin refluxed from the stomach can easily penetrate the epithelial layer and stimulate noxious receptors on the afferent neurons and induce reflux symptoms [5] . An association between widened intercellular spaces and reflux symptoms has been reported [11,12] . In order to enter the mucosal intercellular spaces, acid and pepsin have to penetrate the intercellular adhesion sites of the uppermost superficial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order for acid and pepsin to penetrate into the intercellular spaces, the intercellular adhesion of the uppermost squamous epithelial cells needs to be damaged or widened [5,9,10] . Several reports have described the widening of intercellular spaces between squamous epithelial cells in mid-stratified epithelial layers by using transmission electron microscopy (TEM) [9][10][11][12] . However, there has been no description of intercellular adhesion between cells located in the uppermost part of the stratified squamous epithelium, since intercellular spaces of esophageal superficial epithelium could not be observed by TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Acid perfusion in the esophagus can provoke a dilated intercellular space, 13,21,22 and most patients achieve recovery from this dilation after PPI therapy. 23,24 Thus, it can be easily speculated that the low IB of the distal esophagus in globus patients is the consequence of acid injury to the esophageal mucosa. In addition to the lower IB of the distal esophagus, the IB values in the proximal esophagus at positions 15 and 17 cm from the LES in the acid reflux patients were lower than those in the other 2 groups, although these findings were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Some researchers have suggested that DIS can be used as an objective indicator for NERD. 11,12 However, this method of GERD diagnosis is invasive and costly. Therefore, researchers have shifted their attention toward a simpler and less expensive technique: saliva pepsin testing.…”
Section: Introductionmentioning
confidence: 99%